INCREASING THE MOTIVATION OF PRIMARY SCHOOL PUPILS THROUGH THE USE OF ICT IN THE EDUCATIONAL PROCESS - Stoitsov, Gencho; Stoitsova, Gergana (International Journal of Research -GRANTHAALAYAH, 2019)
This article presents a pedagogical study on the impact of Information Communication Technologies (ICT) on the motivation of primary school pupils in math classes. The obtained results demonstrate the positive impact of ICT on learning motivation.